2020
DOI: 10.17478/jegys.651436
|View full text |Cite
|
Sign up to set email alerts
|

Writing Motivation and The Ability in Writing a Research Proposal of Generation Z Students Based on Cognitive Style

Abstract: This article presents a comprehensive analysis of writing motivation and the ability in writing a research proposals of Generation Z students based on differences in their cognitive styles. The research involved 70 Generation Z students in Faculty of Teacher Training and Education, Universitas Maritim Raja Ali Haji, Indonesia. After going through the Group Embedded Figures Test (GEFT) stages, these students were divided into 2 groups based on their cognitive style, field independent (FI) and field dependent (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
(38 reference statements)
3
6
0
Order By: Relevance
“…It can be concluded that the students with the cognitive style of FD have better ability in the learning outcomes on the concept of understanding than the students with the cognitive style of FI. On the contrary, the students with the cognitive style of FD have the learning outcomes on concept application better than the students with cognitive style (Andheska et al, 2020). This factual evidence supports the previous studies that the cognitive style is important to be one of many considerations in choosing the strategy and the use of instructional media (Margunayasa et al, 2019;Marwazi et al, 2019).…”
Section: Sourcesupporting
confidence: 78%
“…It can be concluded that the students with the cognitive style of FD have better ability in the learning outcomes on the concept of understanding than the students with the cognitive style of FI. On the contrary, the students with the cognitive style of FD have the learning outcomes on concept application better than the students with cognitive style (Andheska et al, 2020). This factual evidence supports the previous studies that the cognitive style is important to be one of many considerations in choosing the strategy and the use of instructional media (Margunayasa et al, 2019;Marwazi et al, 2019).…”
Section: Sourcesupporting
confidence: 78%
“…Language skills such as reading and writing are closely related to critical thinking activities (Ataç, 2015;Dewi et al, 2019). It is also in line with research which states that there is a very close relationship between quality writing and critical thinking skills (Andheska et al, 2020;Hunanda Kuswandari, 2018;Sinaga & Feranie, 2017). Before knowing how students can put their critical thinking skills into oral and written language, they certainly need to know about their critical thinking abilities (Abdurrahman et al, 2019).…”
Section: Introductionsupporting
confidence: 78%
“…The critical thinking ability is able to help students reasoning to solve problems (Jatmiko et al, 2018). At universities, students must pass the classes with good grades and be able to solve all academic and personal problems (Andheska et al, 2020). Therefore, students need to develop their critical thinking skills in facing various academic difficulties (Marni̇ et al, 2019;Serin, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the study found that the learning styles that exist in the young gifted students in Islamic learning both urban and rural are very diverse, and obtained high scores both auditory, visual and kinesthetic. This indicates that learning styles in young gifted children have a variety of learning (Andheska, Suparno, Dawud & Suyitno, 2020), and does not depend on one learning style (Kuo, Maker, Su & Hu, 2010;Mooij, 2013). Of course, this is very good for young children who are gifted, where they can be easily guided by teachers with a variety of diverse methods and approaches to learning.…”
Section: Discussionmentioning
confidence: 94%